Leishmania donovani Utilize Sialic Acids for Binding and Phagocytosis in the Macrophages through Selective Utilization of Siglecs and Impair the Innate Immune Arm - Roy, Saptarshi; Mandal, Chitra (PLOS Neglected Tropical Diseases, 2016)
Author Summary Sialic acids are nine carbon sugars present on terminal cell surface glycoproteins and glycolipids. Siglec is a membrane receptor that belongs to an immunoglobulin super family present in almost all the haematopoetic cell lineages. There are 14 different types of siglecs present on human immune cells that take an active part in balancing the magnitude of immunological reactions. In general, these siglecs bind with sialic acids and negatively regulate the immune response. Leishmania contains sialic acids on its surface. Virulent parasites utilize this sugar to bind with macrophages through siglec-1 and siglec-5 compared to low sialic acids containing avirulent parasites. Such sialic acids-siglec-mediated interactions exhibited a suppressed host immune response which helped them to establish successful infection compared to desialylated virulent and avirulent parasites, as well as, siglec-depleted macrophages. Interestingly, interaction between sialic acids and siglec-1 induced enhanced phagocytosis, while sialic acids-siglec-5 interaction upregulated the phosphatase SHP-1. This interaction with the virulent strain exhibited deactivation of various downstream signaling pathways and ultimately controlled translocation of a functional component of transcription factor NF-κβ for regulation of cytokines and other effector molecules in infected macrophages. Thus, the interaction between the parasite and the host cells through sialic acids-siglec binding is clearly a newly identified mechanism by which parasites can establish successful infection by subverting the host’s innate immune response.